Short Term Outcomes of Single Anastomosis Sleeve Ileal (SASI) Bypass - Al Baaj, Safauldeen Salim; Dulaimi, Hazim Kareem Nassr; Altameemi, Mohammed Abdulkareem Abboodi (Academic Journal of Clinicians, 2024)
Background: Single Anastomosis Sleeve Ileal (SASI) bypass is a successful weight loss surgery together with a great impact on metabolic syndrome. is a new emerging bariatric surgery procedure with current debates on its efficacy and safety. Aim of the Study: Is to evaluate the efficacy and safety of SASI bypass surgery for treatment of obesity. Patients and methods: The study has been carried out in Al Sadder Teaching Hospital and other private hospitals in Al-Najaf Al Ashraf from 2018 to 2019. A total of 33 patients were included in this study, of whom 25 were female and 8 were male. All patients underwent SASI bypass surgery and short term followed up post operatively. Its impact on BMI change, excess weight loss (%EWL), and associated problems were reported post operatively. The study was done as a single group case control study. Results: The mean EWL was 93.2% over 12 months, 9 patients were Diabetes who got remission. 23 patients were got improvement in hyperlipidemia, in addition, 5 patients diagnosed with fatty liver and reversal surgery were did for them. Three patients were died suddenly after 12 months, two of them without any approval cause and one of them might be from liver failure. 5 patients underwent reversal surgery due to undesirable weight loss. Conclusion: Single Anastomosis Sleeve Ileal (SASI) is provisional effective procedure especially for super obesity patients (BMI>50 kg/m2) but its associated with significant complication.